PENGARUH LINGKUNGAN KERJA, STRES KERJA DAN BEBAN KERJA TERHADAP KINERJA KARYAWAN PT. FORISA NUSAPERSADA LAMONGAN - Miftahul Huda; Moh. Azus Shony Azar (LPPM UNISDA, 2021)
This study aims to determine the Work environment, work stress and workload on the performance of PT. Forisa Nusapersada Lamongan employees. The hypothesis proposed in this study are: a). Work environment influences the performance of PT Forisa Nusapersada Lamongan employees. b). Job stress affects the performance of PT Forisa Nusapersada Lamongan employees. c). Workload affects the performance of PT Forisa Nusapersada Lamongan employees.The population in this study were all employees who were in PT Forisa Nusapersada Lamongan as many as 97 people. The sample used was 97 respondents. The sampling technique used in this study was to use the